Healthcare utilization and costs for patients with Parkinson’s disease in Taiwan - Kuan-Chen Chen; Li-Jung Elizabeth Ku; Ya-Hui Hu; Yu Sun; Alexis Elbaz; Pei-Chen Lee (BMC Neurology)
Abstract Background Parkinson’s disease (PD) exerts a considerable burden on the elderly. Studies on long-term costs for Parkinson’s disease patients in Taiwan are not available. Objectives This study aims to examine the medical resource utilization and medical costs including drug costs for PD patients in Taiwan over up to 15 years of follow-up. Methods Incident PD patients and matched non-PD subjects were identified between 2003 and 2016 from the National Health Insurance (NHI) research database. Differences in annual healthcare utilization and costs between PD and non-PD subjects from 2003 to 2018 were predicted by generalized linear models. We performed analyses stratified by PD severity and also by age, gender, and duration of follow-up. Results We identified 50,290 PD cases and 201,153 non-PD subjects. From the payer’s perspective, the average total medical costs (drug costs) associated with PD and non-PD subjects were NT$631,080 (NT$222,810) and NT$480,880 (NT$140,120), respectively. Total medical and drug costs of PD after diagnosis remained high, from NT$138,487 per patient in the first year following diagnosis up to NT$154,676 per patient at year 15. The largest components of costs were for outpatient care (55% of total medical costs), and total drugs cost (35% of total medical costs). Patients with severe PD incurred higher total medical costs compared to those with moderate or mild PD, with outpatient and inpatient costs as well as drug costs rising with disease severity. Conclusions This is the first study of its kind in Taiwan that comprehensively analyzes long-term healthcare utilization and costs among PD patients. PD imposes a significant economic burden in Taiwan, with medical (drug) costs being 1.31 (1.59) times that of non-PD individuals and costs increasing substantially with PD severity. Our findings can aid health policymakers in understanding the healthcare needs and medical costs of PD patients, supporting effective policy formulation.